Teknik Penangkapan Menggunakan Jaring Hela Udang Berkantong Pada KM.SPL IX Milik PT. Sinar Pesona Laut - Tomasila, Leopold A.; Pattinaja, Yvonne I.; Farid, Muhamad; Tuhumena, lolita loli (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2024)
This research aims to find out about fishing techniques with pocket shrimp nets at FB. SPL IX. Methods of data collection carried out in the form of observation, interviews and documentation. The data analysis method used is descriptive qualitative and quantitative. The fishing technique with pocket shrimp nets at FB. SPL IX consists of several stages, activities at the fishing base, heading to the fishing ground, activities at the fishing ground, lowering fishing gear (setting), towing fishing gear, hauling, and handling the catch. Techniques for handling fish caught on board Shrimp Hela Nets at FB. SPL IX consists of 8 stages, namely sorting the shrimp and fish, sorting the size of the shrimp, weighing the shrimp, putting it into the inner, putting it on the carton, insulating the carton, putting it in the freezer (ABF/snep) and putting it in the storage hatch. The total production of the catch is 18,218 tons